The Influence of Internal Control toward Production Cost Control Efectivity - Sarjito Surya (UBL, 2013)
One of thelargest componentsofcostsin thecompanyisthe productioncost. Productioncostsare easier to controlbecause it involves theinternalactivities ofthe companyso that obtaining the productioncost in controllingcosts is top priority. The successof a companyto controlproduction costwill bea positive impact oncorporateearningsandincreasing inthe companys objective. Cost ofproductionis one of thecompaniesthatrequirecontrolcash outcarefully and is theexistence of anadequateinternalcontrol. Companies shouldbe awarethatby applyingan adequatesystem ofinternal control, to effectivelycontrolproduction costsandalsoincrease its profit. Thispurposeof thispaperis formeasuringtheinfluenceofinternalcontrolefectivitytowardproductioncost control.